2020
DOI: 10.1101/2020.06.01.127019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

INSIGHT: a population scale COVID-19 testing strategy combining point-of-care diagnosis with centralised high-throughput sequencing

Abstract: We present here INSIGHT (Isothermal NASBA-Sequencing based hIGH-througput Test): a two-stage COVID-19 testing strategy, using a combination of an isothermal NASBA reaction and next generation sequencing. From commercially acquired human saliva with spiked-in viral RNA as input, the first stage employs isothermal amplification of viral RNA to give a rapid result in one to two hours, using either fluorescence detection or a dipstick readout, whilst simultaneously incorporating sample-specific barcodes into the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous reports have also highlighted the importance of primer design and optimization to achieve efficient NASBA. 22,42,43 We observed that primers with fairly similar basic criteria showed significantly different NASBA efficiencies. Therefore, after an initial round of screening for sensors, and zeroing in on an efficient sensor, we again screened for the most efficient NASBA primers for the selected sensor.…”
Section: Discussionmentioning
confidence: 77%
“…Previous reports have also highlighted the importance of primer design and optimization to achieve efficient NASBA. 22,42,43 We observed that primers with fairly similar basic criteria showed significantly different NASBA efficiencies. Therefore, after an initial round of screening for sensors, and zeroing in on an efficient sensor, we again screened for the most efficient NASBA primers for the selected sensor.…”
Section: Discussionmentioning
confidence: 77%
“…We believe that our approach, and future improvements and modifications thereof, might form the basis for such an improvement of several orders of magnitude relative to current testing strategies. Specifically, the ability to pool hundreds or thousands of samples as early as possible, without losing the sample-specific information, is a crucial improvement on all currently published NGS-based tests 6,23,24,25,26,27 . The early pooling approach proposed here, which might be applicable to other protocols, elicits proportional reductions in costs and labor that directly translate to higher throughput in testing.…”
Section: Discussionmentioning
confidence: 99%
“…151 It is noteworthy that other isothermal amplification techniques (some of which will be discussed below) are also in existence and have been used for viral detection, for instance: recombinase polymerase amplification (RPA); 152 rolling cycle amplification (RCA); 153 and nucleic acid sequence-based amplification (NASBA). 154 We will discuss LAMP as an exemplar. One key benefit of this method over traditional PCR is that it is an isothermal reaction, and hence can be run in simple setups without the need for a thermocycler.…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%